Strategic Management of Schools for Excellence: Integrating Quality Culture and Character Development in Leading Educational Institutions - Ismatul Izzah; Mulyadi Mulyadi; Muhammad Walid; Moh Padil; Aji Wahyudin (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates strategic management practices in two high-achieving Indonesian schools, focusing on how they integrate quality culture and character development. With increasing emphasis on holistic education, this research explores how different management strategies can balance academic excellence with character formation. A qualitative descriptive approach using a case study design was employed to provide a deep understanding of these schools' management practices. Data were collected through in-depth interviews, observations, and document analysis, involving principals, teachers, management staff, students, and parents to gain multiple perspectives on school policies, teaching methods, and learning experiences. The findings reveal that both schools implement strategic management effectively, though with distinct approaches. SMA Unggulan Hafshawaty Zainul Hasan BPPT Genggong prioritizes spiritual and moral development through structured programs grounded in religious values, shaping students’ character. Conversely, SMA Tunas Luhur Paiton Probolinggo emphasizes educational technology to enhance learning quality, incorporating digital tools that also support character development. These results highlight the role of visionary and adaptive leadership in aligning strategic management with educational goals, demonstrating that both religious and technological approaches can effectively balance academic and character growth. This study contributes to educational management by offering a model for integrating quality culture and character development, adaptable to various school contexts. By combining spiritual, moral, and technological strategies, schools can enhance both academic success and character formation, providing a comprehensive educational approach.